Stealthing and Sexual Consent: Addressing Non-Consensual Condom Removal and Survivor Support on College Campuses - Monideepa B. Becerra (Sexes, 2025)
Stealthing, the nonconsensual removal of a condom during sexual intercourse, is a prevalent yet underreported form of sexual misconduct, particularly among college students. This white paper examines the legal landscape, gaps in responses, and the burden of stealthing on college students. It presents actionable strategies for college campuses to combat stealthing, including updating policies, enforcing a zero-tolerance policy, training staff, providing survivor-centered support services, integrating cultural competency, and ensuring transparent enforcement of processes. These strategies aim to empower college campuses to prevent and reduce stealthing, promote informed consent, and enhance survivor support.